Biochemical investigations of human papillomavirus‐infected cervical fluids. Issue 3 (29th December 2014) - Choi, Samjin; Park, Hun‐Kuk; Min, Gyeong Eun; Kim, Yeon‐Hee
ABSTRACT Purpose: Cervical cancer is caused by persistent infection with high‐risk types of human papillomavirus (HPV). The aim of this study was to investigate the potential of Raman spectroscopy as a stand‐alone analytical tool for clinical diagnosis of HPV infection using human cervical fluids. Method: A drop‐coating deposition surface‐enhanced Raman scattering (DCD‐SERS) method was identified as the most effective method of biochemical analysis in cervical biofluids. Results: Using a 2‐µL sample, the proposed DCD‐SERS method yielded Raman spectra with high reproducibility, noise‐independence, and uniformity. Additionally, the produced spectra were independent of the volume of fluid used and detection zone analyzed within the central and the ring zones. The optical detection of HPV infection in cervical fluids could be detected accurately in the central zone. Different Raman spectra were obtained according to HPV type. In particular, HPV‐16 and HPV‐18, which are the major risk factors for cervical cancer, showed a distinct spectral difference in cervical fluids, with a similar pattern for high Raman bands at >1, 000 cm−1 but a different pattern for low Raman bands at <1, 000 cm−1. Therefore, all ranges of HPV‐gated DCD‐SERS could be used to detect the presence of HPV infection. Conclusions: Raman spectroscopy provides a good alternative method for early clinical diagnosis of HPV infection, and we are hopeful that this proposed method of HPV assessment will be approved for use in obstetrics and gynecology clinics. Microsc. Res. Tech., 2014. © 2014 Wiley Periodicals, Inc. Microsc. Res. Tech. 78:200–206, 2015. © 2014 Wiley Periodicals, Inc.